2020
DOI: 10.1186/s41232-019-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Toward the realization of cardiac regenerative medicine using pluripotent stem cells

Abstract: Heart transplantation (HT) is the only radical treatment available for patients with end-stage heart failure that is refractory to optimal medical treatment and device therapies. However, HT as a therapeutic option is limited by marked donor shortage. To overcome this difficulty, regenerative medicine using human-induced pluripotent stem cells (hiPSCs) has drawn increasing attention as an alternative to HT. Several issues including the preparation of clinical-grade hiPSCs, methods for large-scale culture and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Induced pluripotent stem cell (iPSC)-derived cardiomyocytes represent an ideal cell source for cardiac regeneration. However, there is no consensus on which differentiation protocol and cell stage are most suitable for eliciting a beneficial effect after transplantation [11,12], while the immunogenicity of the cells at the various differentiation stages is also not known. Therefore, the transplantation of syngeneic neonatal cardiomyocytes allows us to reproducibly study the beneficial effects of cardiomyocytes without the involvement of a transplant rejection response by the host immune system obscuring the effect of cell transplantation on the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cell (iPSC)-derived cardiomyocytes represent an ideal cell source for cardiac regeneration. However, there is no consensus on which differentiation protocol and cell stage are most suitable for eliciting a beneficial effect after transplantation [11,12], while the immunogenicity of the cells at the various differentiation stages is also not known. Therefore, the transplantation of syngeneic neonatal cardiomyocytes allows us to reproducibly study the beneficial effects of cardiomyocytes without the involvement of a transplant rejection response by the host immune system obscuring the effect of cell transplantation on the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, induced pluripotent stem cell (iPSC) technology has become a major technology in cardiovascular research as it enables efficient in vitro generation of functional cardiomyocytes (CM) without any ethical concerns. CM derived from iPSCs have been shown to be suitable for regenerative therapies and drug development [1][2][3]. However, the proper maturation is a common problem as iPSC-CM do not display the same morphological and functional features as their adult counterparts, rather resembling fetal CM [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Following image acquisition and data reconstruction, sarcomere length and z-disc thickness were determined. Sarcomere length was evaluated by measuring the distance between intensity peaks, corresponding to adjacent α-actinin labelled filaments(1)(2)(3)(4)(5). z-disc thickness was automatically analyzed, and the mean width of each filament was calculated.…”
mentioning
confidence: 99%
“…Among the different stem cells available for potential application in cardiac regenerative medicine there are skeletal myoblasts [ 102 ], bone-marrow derived cells [ 103 ], endothelial stem cells [ 104 ], mesenchymal stem cells [ 105 ], adipose-derived stem cells [ 106 ], cardiac stem cells [ 107 ], and pluripotent stem cells [ 108 , 109 ]. iPSCs, with their ability for self-renewal and their capability to differentiate into any cell type, without the risk of post-transplantation immune rejection, represent the ideal candidate for regenerative medicine [ 110 ]. Different studies have demonstrated the benefit and efficacy of iPSC-derived CMs in restoring compromised cardiac function and morphology [ 111 , 112 , 113 , 114 ].…”
Section: Cardiac Regenerative Medicinementioning
confidence: 99%